Sympathetic reactivity to experimentally induced stress in alexithymia - Martínez Sánchez, Francisco; Ato García, Manuel (Anales de Psicología / Annals of Psychology, 2011)
Alexithymia refers to a specific disturbance in emotional processing that is manifested through difficulties in identifying and verbalizing feelings. The main objective of this research has been the study the relationship between sympathetic reactivity patterns, measured by electrodermal activity, and the alexithymia level, in a stressful laboratory situation. The subjects were high- or low-alexithymic young females (separated by TAS-20). The experiment involved six phases and the sympathetic reactivity was assessed in each one of them, using the Palmar Sweat Index (PSI), a sensitive indicator of the number of active sweat glands. The results show that both alexithymic and non-alexithymic subjects showed significant increases in PSI during stress phases and systematic decreases in all relaxation phases. We also obtained significant differences between TAS-20 low and high scores and between aggregated experimental phases, but no evidence of interaction TAS-20 x experimental phases. The results provide little support with the hypothesis that alexithymic subjects are more physiologically reactive to stress.